Association of gastrointestinal events and osteoporosis treatment initiation in newly diagnosed osteoporotic Israeli women. Issue 9 (17th August 2015) - Yu, J.; Goldshtein, I.; Shalev, V.; Chodick, G.; Ish‐Shalom, S.; Sharon, O.; Modi, A.
Summary Background The objective was to examine the association of gastrointestinal (GI) events and osteoporosis treatment initiation patterns among postmenopausal women following an osteoporosis diagnosis from an Israeli health plan. Methods This retrospective analysis of claims records included women aged ≥ 55 years with ≥ 1 osteoporosis diagnosis (date of first diagnosis was index date). Osteoporosis treatment initiation was defined as use of osteoporosis therapy (oral bisphosphonates or other) during 12 months postindex. GI events (diagnosis of GI conditions) were reported for 12 months preindex and postindex (from index to treatment initiation or 1 year postindex, whichever occurred first). The association of postindex GI events (yes/no) with the initiation of osteoporosis treatment (yes/no) and with type of therapy initiated (oral bisphosphonate vs. other) were examined with logistic regression and Cox proportional hazard regression (as sensitivity analysis). Results Among 30, 788 eligible patients, 17.5% had preindex GI events and 13.0% had postindex GI events. About 70.6% of patients received no osteoporosis therapy within 1 year of diagnosis, 24.9% received oral bisphosphonates and 4.5% received other medications. Postindex GI events were associated with lower odds of osteoporosis medication initiation (85–86% reduced likelihood; p < 0.01). Upon treatment initiation, postindex GI was not significantly associated with the type of osteoporosis therapy initiated, controlling for baseline GI events and patient characteristics. Conclusions Among newly diagnosed osteoporotic women from a large Israeli health plan, 70.6% did not receive osteoporosis treatment within 1 year of diagnosis. The presence of GI events was associated with reduced likelihood of osteoporosis treatment initiation.